Comparison of single spot urinary albumin-creatinine ratio with 24-hour urinary protein excretion in women with preeclampsia - Kaul, Indu; Bhagat, Bawa Ram; Sharma, Deepika; Singh, Gagan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The measurement of albumin: creatinine ratio (ACR) in a spot urine sample avoids the influence of variation in urinary solute concentration and provides a more convenient and rapid method to assess protein excretion. The aim of this study was to evaluate urinary spot ACR as a new marker for proteinuria and to study its correlation and accuracy in comparison with 24-hour urinary protein. Methods: The prospective one-year study was conducted on 100 pregnant women, 18-40 years, >20 weeks gestation with a diagnosis of preeclampsia. A spot midstream urine sample was taken for detection of albuminuria by dipstick method. Another spot sample was taken for detection and calculation of spot ACR. The 24-hour urine collection was taken immediately afterward to evaluate 24-hour urinary protein excretion. Results: A positive linear relation exists between ACR and 24-hour urinary protein excretion The ROC revealed cut-off of 20.4 with 88.5% sensitivity, 75% specificity, 98.8% positive predictive value and 21.4% negative predictive value. Spot urinary ACR >20.4 correctly identified women having 24-hour urinary protein excretion in excess of 0.3 gm/DL. Conclusions: A strong correlation exists between single spot urinary ACR with 24-hour urinary protein excretion in women with preeclampsia.